"Sempre os outros ditaram o que eu sou, eu sempre estive refém": implicações da ofensiva conservadora para a saúde mental da população LGBTI+ no Brasil - Silva, Jardson (2025)
The conservative offensive consolidated through the 2016 parliamentary coup in Brazil, the rise of Bolsonaro (PL) to the presidency in 2018, and the construction of Bolsonarism, has impacted the various dimensions of social life. Its repercussions can be identified in the various retractions of rights that the working class has experienced in recent years, as well as through the resurgence of expressions of violence that materialize the processes of exploitation/oppression in different forms, such as through the increase in the genocide of the black population, femicide and hate crimes against the LGBTI+ population. For people who direct their affective-sexual life outside of cisheterosexuality, sociocultural and historical elements, based on the structure of capitalist, racist and cisheteropatriarchal society, deepen the scenario of violence and violation of rights, which, associated with the advancement of the neoliberal-conservative project, accentuate the processes of psychological suffering of these individuals, since there is a reality of prejudice, discrimination, death, fear, dehumanization and oppression. In this sense, we aim with this dissertation to analyze the implications of the conservative offensive and the reproduction of violence, in the context of Brazilian capitalist, racist and cisheteropatriarchal society, for the mental health of the LGBTI+ population. As specific objectives, we seek to understand the process of conservative offensive orchestrated by the rise of Bolsonarism in Brazil and its consequences for the LGBTI+ population; to identify the expressions of violence against LGBTI+ people, the main violating agents and their relationship with the processes of psychological suffering; to investigate the relationship between the living and existence conditions of the LGBTI+ population and the production of psychological suffering; and to analyze the impacts of LGBTIphobic violence on the mental health of these individuals. To this end, anchored in historical-dialectical materialism, we present a quantitative-qualitative study, in which we resorted to bibliographic and documentary research and semi-structured interviews, which were conducted with users of the Municipal LGBT Citizenship Center of Natal/RN. Regarding the documentary analysis, we used data from the Reports on Violent Deaths of LGBTI+ and the Dossier on Deaths and Violence against LGBTI+, produced, respectively, by the Gay Group of Bahia and the Observatory of Deaths and Violence against LGBTI+ in Brazil, with the time frame from 2018 to 2023. In view of this, we learned that the conservative offensive, by propagating hate speech, violence and revitalizing a political agenda of setbacks, delegitimizes sexual and gender diversity, aspects that, based on the material bases of this sociability, impact not only the reproduction of LGBTIphobic violence, but also the subjectivity of these individuals, since these are dimensions that are conditioned by the objective conditions that shape social relations. It is noted, therefore, that this scenario produces suffering forged in the constant violations of rights, requiring that the fight for mental health be not dissociated from the horizon of overcoming this sociability.